A Description of Spina Bifida Cases and Co-Occurring Malformations, 1976–2011 - Parker, Samantha E. (Am J Med Genet A, 2013)
Mandatory folic acid fortification in the United States corresponded with a decline in the prevalence of spina bifida (SB). The aim of this study was to describe the epidemiologic characteristics of isolated versus non-isolated SB cases in both pre- and post-fortification periods. SB cases in the Slone Epidemiology Center Birth Defects Study from 1976 to 2011 without chromosomal anomalies and syndromes were included. A maternal interview, conducted within 6 months of delivery, collected information on demographics, reproductive history, diet, and supplement use. Daily folic acid intake in the periconceptional period was calculated using both dietary and supplement information and categorized as low intake (<400 μg/day) or high intake (≥400 μg/day). SB cases (n=1170) were classified as isolated (80.4%) or non-isolated (19.1%). Non-isolated cases were further divided into subgroups based on accompanying major malformations (midline, renal, genital, heart, laterality). Compared to non-isolated cases, isolated cases were more likely to be white, non-Hispanic and have more than 12 years of education. Cases in the renal, genital, and heart subgroups had the lowest proportions of mothers with a high folic acid intake. The change from pre- to post-fortification was associated with a decrease in the proportion of isolated cases from 83% to 72%, though in both periods isolated cases were more likely to be female and their mothers were more likely to have high folic acid intake. These findings highlight the importance of separating isolated and non-isolated cases in etiologic research of SB.